A comparison study of the detection of bloodstains on painted and cleaned surfaces with luminol. (August 2018) - Brenzini, Valentina; Pathak, Rahul
Highlights: Bloodstains concealed with solvent based paint need a lower number of layers. Distinctive patterns in the surface of the tile when observed under the microscopy. Bleach tiles gave a general luminescence on the whole surface. More layers of paint were necessary where the bloodstains were not cleaned. Abstract: There seems to be a limited amount of research about the detection of concealed bloodstains on painted surfaces. The bloodstains on walls and floors are often removed by cleaning, in some cases the surfaces are painted by the perpetrator after committing a violent crime in order to hide the crime that has occurred. The study hereafter extends and deepens on previous researches by investigating the detectability of horse bloodstains on painted ceramic tiles as a function of the number of layers of paint. In this study luminol was used as a reagent to detect the bloodstains. The study focuses on two types of paints: water based and solvent based paint. This study also investigates the effectiveness in reducing the detectability of bloodstains on ceramic tiles using four different cleaning methods pure water, soap with water, wet wipes, and bleach. In the experiment the bloodstains were cleaned at various intervals of time after the deposition (two minutes, fifteen minutes and one hour). The study concluded that the bloodstains concealed by layers of solvent based paint are less likely to be detected by luminol compared to water based paint. The study also concluded that the tiles cleaned with bleach are recognisable from the other ones cleaned using other methods. In each study the duration of the reaction was timed, highlighting the differences in the cleaning methods.